Illocutionary Acts of Donald Trump's Speech in The Capitol Building Washington DC - Khanafi, Rusid; Mahmud, Murni; Abdullah, Abdullah (Har Press Indonesia, 2023)
This article investigated and examined the illocutionary forms in Donald Trump's speech at the Washington DC Capitol building and explore the illocutionary functions of each of these utterances. This research was conducted with a qualitative descriptive design. Data for research, this is from Youtube about two months ago. about Donald Trump's inauguration speech. The research data is the explanation and intent of Donald Trump's speech at the inauguration via YouTube. The survey results show that: 1) There are five types of illocutionary in Donald Trump's inauguration speech on YouTube: representative, directive, commissive, expressive, and declarative. 2) Categories found in Donald Trump's speech: stating, demanding, concluding, suggesting, commanding, promising, ordering, liking, mourning, and declaring. It can be concluded that in this study there are many illocutions in Donald Trump's speech so that he is able to convey the same or different meaning in the speech.